Sustainable Development of University as a Prerequisite of Region’s and Country’s Prosperity - A. V. Timiryasova (Высшее образование в России)
The article by the rector of the Kazan Innovation University named after V.G. Timiryasov (KIU) shows the development path of one of the strongest non-governmental universities in the Volga region, recognized as a university that makes a great contribution to the development of the region and the country. This academic year, KIU celebrated its 25th anniversary. The demand for a university among the population is evidenced by the fact that, according to the ranking of the demand for universities in the Russian Federation, published by the Social Navigator project of MIA Russia Today, the university takes the 15th place in the group “Universities of management area” (Economics, Finance, Law). The share of graduates of KGU named after V.G. Timiryasov who received a job placement is 88,9%. The share of funds from the commercialization of intellectual products is 10,9%. Also, the ranking shows a high citation index of the works of faculty. The development of the university is comparable to the development of the largest universities in the world, which, by training personnel in popular specialties, provide the future for the country.